William Shakespeare's The merry wives of Windsor - Shakespeare, William, 1564-1616; Landen, Dinsdale; Le Touzel, Sylvestra; Downie, Pennie; Woodeson, Nicholas; Jackson, Philip; Swift, Clive; Brill, Clive (Auburn, CA : Audio Partners, 2003)
The dissolute Sir John Falstaff plans to seduce Mistress Ford and Mistress Page, two "Merry wives of Windsor", thereby gaining access to their husbands' wealth.
Compact discs.
Unabridged.
"A companion to The complete Pelican Shakespeare"--Container.
Recording originally published 1998.
Plot synopsis and complete cast list in container.
Director, Clive Brill; composer, Dominique Le Gendre.
Keywords: Married women -- Drama; Falstaff, John, Sir (Fictitious character) -- Drama; English drama (Comedy); Windsor (Berkshire, England) -- Drama